2019
DOI: 10.1590/0103-8478cr20190064
|View full text |Cite
|
Sign up to set email alerts
|

Plant essential oils against bacteria isolated from fish: an in vitro screening and in vivo efficacy of Lippia origanoides

Abstract: The use of natural products, such as essential oils (EOs), is a potential novel approach to treat fish bacterial infections with a lower risk of developing resistance. There has been a number of studies reporting the activity of EOs as those obtained from the species Achyrocline satureioides, Aniba parviflora, Aniba rosaeodora, Anthemis nobilis, Conobea scoparioides, Cupressus sempervirens, Illicium verum, Lippia origanoides, and Melaleuca alternifolia against bacteria. However, there are few studies investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Similarly, previous studies have verified the ability of the EO of L . alba (De Souza et al, 2017), EOCC (Millezi et al, 2013), citral and carvacrol (Bandeira Junior et al, 2019) to prevent the formation of biofilms of Aeromonas spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, previous studies have verified the ability of the EO of L . alba (De Souza et al, 2017), EOCC (Millezi et al, 2013), citral and carvacrol (Bandeira Junior et al, 2019) to prevent the formation of biofilms of Aeromonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…An additive effect can reduce the time of antibacterial action compared to antimicrobials used alone (Scandorieiro et al, 2016). Bandeira Junior et al (2019) found that citral and carvacrol had an additive effect with florfenicol against A . hydrophila .…”
Section: Discussionmentioning
confidence: 99%
“…A strong inhibitory effect of Ocimum basilicum EO with 3 µL/mL and 9 µL/mL MIC values was reported on A. hydrophila and A. veronii, respectively [105]. Among nine different herb EOs, Conobea scoparioides and Lippia origanoides EOs had remarkable activity against A. hydrophila with the low respective MIC and MBC values of 200 µg/mL [106].…”
Section: Oligohymenophorea Ichthyophthirius Multifiliismentioning
confidence: 97%
“…Pirog et al (2019) found that essential oils combined with other antimicrobials could destroy yeast and bacterial biofilm, thereby significantly decreasing their MIC [61]. Bandeira Junior et al (2019) also found that carvacrol had an additive effect with florfenicol on A. drophila [62]. In this investigation, the antibacterial activity of carvacrol combined with neomycin sulfate showed an additive effect, suggesting that a combination of conventional antibiotics with carvacrol is a promising alternative for the control of A. hydrophila infection in aquaculture.…”
Section: Discussionmentioning
confidence: 52%